Berani Berkata Tidak”: Edukasi Pencegahan Kekerasan Seksual pada Anak SD di SDN 010 Batam Kota Kecamatan Belian - Ridni Husnah; Erika Fariningsih; Fitriani Fitriani; Dita Cahya Olivia; Nanda Noor Muhammad Nasution (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2026)
Sexual violence against children is a serious issue that affects their physical, psychological, and social development. Limited knowledge of self-protection increases children's vulnerability to sexual abuse, highlighting the need for age-appropriate preventive education. This community service program aimed to improve elementary school students' knowledge and self-protection skills through the "Dare to Say No" program. The activity was conducted at SDN 010 Batam Kota, Belian District, Batam City, involving 40 students from grades IV, V, and VI. The program employed observation, Focus Group Discussions (FGDs), interactive education, demonstrations, role-playing, and pretest-posttest evaluations. The implementation adopted a Participatory Action Research (PAR) approach with community organizing strategies involving school principals, teachers, and students throughout the program. The results demonstrated a significant improvement in participants' knowledge, with the average score increasing from 58.25 in the pretest to 86.75 in the posttest. Students also showed better understanding of safe and unsafe touch, greater confidence in refusing inappropriate behavior, and increased awareness of reporting incidents to trusted adults. Furthermore, the program strengthened teachers' roles in child protection education and encouraged the school's commitment to creating a safe and child-friendly learning environment. Overall, the "Dare to Say No" program proved effective in enhancing children's knowledge, self-protection skills, and awareness regarding sexual violence prevention. Sustainable implementation involving schools, parents, health professionals, and other stakeholders is recommended to reinforce school-based child protection systems.